2017
DOI: 10.1021/acs.jpcc.7b08039
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots from a Single Source Exhibiting Tunable Luminescent Colors through the Modification of Surface Functional Groups in ORMOSIL Films

Abstract: A simple strategy to fabricate carbon dots (CDs) incorporated organically modified silica (ORMOSIL) films exhibiting tunable tricolor emission has been accomplished. First, the green-emitting CDs with excitation-independent nature and high quantum yield were prepared from o-phenylenediamine in ethanol by solvothermal method. These CDs after purification were dispersed in ORMOSIL sol, and their photoluminescence wavelengths were tuned to three intense luminescent colors (orange, yellow, and green) by adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…The carbon underlayer has been produced from carbon dots using biomass as raw material through a facile hydrothermal process. Carbon dots feature unique photoluminescence, electron trapping and electron transfer properties, 38,39 are stable, low cost, nontoxic and easy to prepare. 40 Hematite (α-Fe 2 O 3 ) is considered one of the most exceptional photoanode candidates due to its nearly ideal bandgap, abundancy, nontoxicity, and chemical and photo stability.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon underlayer has been produced from carbon dots using biomass as raw material through a facile hydrothermal process. Carbon dots feature unique photoluminescence, electron trapping and electron transfer properties, 38,39 are stable, low cost, nontoxic and easy to prepare. 40 Hematite (α-Fe 2 O 3 ) is considered one of the most exceptional photoanode candidates due to its nearly ideal bandgap, abundancy, nontoxicity, and chemical and photo stability.…”
Section: Introductionmentioning
confidence: 99%
“…The peak binding energy of 530.6 eV, 399.2 eV, 284.5 eV were assigned to O, N, C, respectively. Furthermore, peaks observed at 933.4 eV and 953.3 eV corresponds to the spin‐orbit splitting component of Cu 2p 3/2 and Cu 2p 1/2 , respectively, along with a satellite peak at 942 eV, which confirms the presence of Cu(II) in the CuO@CB[6] nanocomposite …”
Section: Resultsmentioning
confidence: 97%
“…Figure S4B (Supporting Information) shows that curcumin exhibited a fluorescence emission maximum centered at a wavelength of ≈450 nm upon excitation at a wavelength of 365 nm in water with a quantum yield (QY) of 0.3%, as assessed by comparison with quinine (QY, 53%) in 0.1 m H 2 SO 4 . Unlike most CQDs, [33][34][35][36][37] the Cur-CQDs ( Figure S4C, Supporting Information) did not exhibit excitation-dependent emission properties. However, we noted that the most purified Cur-CQDs exhibited similar solvent polarity-and pH-dependent fluorescence properties to curcumin ( Figure S5, Supporting Information), implying that curcuminlike structures are indeed present on the surfaces of CQDs.…”
Section: Synthesis and Characterization Of Curcumin-derived Carbon Qumentioning
confidence: 99%
“…[36] Many reports have suggested that nitrogen incorporated (doped) as pyridinyl, pyrrolyl, and amide moieties into the heterocyclic ring systems in CQDs can eliminate nonradiative electron−hole recombination centers from carboxyl and epoxy groups, thereby boosting the fluorescence QY of CQDs. [36,37] Although low fluorescent QY of CQDs is unfavorable to its tracking in vivo, the low QY of Cur-CQDs will not significantly affect its utility as an antiviral agent. We believe that digestion of tissue samples followed by HPLC coupled to UV-vis absorption detection may be the preferred method for the quantitation of Cur-CQDs.…”
Section: Synthesis and Characterization Of Curcumin-derived Carbon Qumentioning
confidence: 99%